An analysis of consumption preference of female students toward female hygiene products as affected by male or female endorsers. - Jemera, Cristy Jane D.; Lumawag, Lorlaine Grace T.; Margallo, Frel Haspy (Miag-ao, Iloilo University of the Philippines Visayas, College of Arts and Sciences, Division of Humanities, 2008)
The study is about the consumption preferece of female students toward female hygiene products as affected by male and female endorsers. It aims to determine how advertisers used male commercial models for female products, identify what kind of female products are using male endorsers, identify the various codes used in the advertisements, determine if the presence of male endorsers could affect the consumption preference of the female consumers and determine who is more effective between the male and female endorser for the female hygiene products. The study was conducted in the three universities of Iloilo City : UPV, WVSU and WVCST. A total of 100 female students served as the respondents of the study. Females are found to be effective endorsers but at the same time having male endorsers as part of the commercial will be helpful.
Thesis (Undergraduate, Bachelor of Science in Broadcasting Communication, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Advertising